2015
DOI: 10.1186/s12889-015-2302-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IgG against plastic resin in workers with and without chemical dermatitis

Abstract: BackgroundThere are many chemical sensitizers which cause allergy in the surrounding environment. However, the identification of substances causing allergy is difficult. We developed a new method to detect IgG which reacts against many kinds of chemical-human serum albumin (HSA) adducts at the same time. In this study, the diagnostic significance of the IgG was studied among workers of a company where a mass outbreak of chemical dermatitis had occurred after changing a plastic resin to a new one.MethodsEleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…We have previously reported that the antibody for Product-X, a mixture of epoxy resin compounds, in human serum can be detected by dot blot assay using X-HSA adducts as the antigen. Moreover, we also showed that the levels of Product-X-specific IgG in human serum are strongly correlated with the onset of dermatitis [9]. In this study, we attempted to simultaneously detect several specific antibodies against chemicals, such as TDI, PA, and FA in human serum from four workers handling plastic resin who had a history of allergy and from five unexposed workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the antibody for Product-X, a mixture of epoxy resin compounds, in human serum can be detected by dot blot assay using X-HSA adducts as the antigen. Moreover, we also showed that the levels of Product-X-specific IgG in human serum are strongly correlated with the onset of dermatitis [9]. In this study, we attempted to simultaneously detect several specific antibodies against chemicals, such as TDI, PA, and FA in human serum from four workers handling plastic resin who had a history of allergy and from five unexposed workers.…”
Section: Resultsmentioning
confidence: 99%
“…Dot blots were performed as previously reported [9]. The antigens were blotted to nitrocellulose membranes (Amersham, GE Healthcare), which were then blocked with blocking buffer (Nacalai Tesque).…”
Section: Detection Of Chemical-specific Iggmentioning
confidence: 99%
“…Importantly, however, it has also been reported to have estrogenic activity, albeit weaker than that of BPA [3]. In our previous study, BADGE-specific IgG was identified in sera obtained from workers with contact dermatitis who had used this material in their working space [4]. This result suggested that serum BADGE-specific IgG could reflect exposure to BADGE and that exposure is related to allergic diseases.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have reported that exposure to endocrine-disrupting compounds (EDCs) including BPA and BADGE might increase the risk of allergic diseases such as respiratory allergies, contact dermatitis, food sensitization, and food tolerance [47]. BPA was suggested to induce a T helper 2 (Th2)-dominated immune response through its estrogenic activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…An ELISA using formaldehyde (FA) and phthalic anhydride (PA)-HSA adducts as a substrate was also reported (Dykewicz et al, 1991;Nielsen et al, 1988). We previously reported a dot blotting-based method for the detection of chemical-specific IgGs, including TDI, FA and PA (Tsuji et al, 2016;Kawamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%